Geology of the footwall of the northern Plomosa Mountains metamorphic core complex, west-central Arizona - Strickland, Evan, author; Singleton, John, advisor; Magloughlin, Jerry, committee member; Coleman, Rocky, committee member (Colorado State University. Libraries, 2017)
The northern Plomosa Mountains is a N-S trending range in the lower Colorado River Extensional Corridor, west-central Arizona – a region which hosts several highly extended terrains known as metamorphic core complexes. Metamorphic core complexes are characterized by low-angle normal faults (detachment faults) which have accommodated tens of kilometers of extension, and juxtapose a brittlely-deformed hanging wall against a ductilely-deformed footwall. The primary structural feature of the northern Plomosa Mountains is the Plomosa detachment fault, a gently-dipping low-angle normal fault. Though 1:24,000 scale geologic mapping had previously been conducted in the northern Plomosa Mountains, little work had been done in the metamorphic footwall of the Plomosa detachment fault, which was the focus of this study. New 1:10,000-scale geologic mapping, structural and microstructural analysis, and U-Pb zircon geochronology reveals that the footwall of the Plomosa detachment fault is dominated by early Miocene mylonitic fabrics associated with detachment faulting, demonstrating that the northern Plomosa Mountains is a metamorphic core complex similar to adjacent core complexes in the region. Three mylonitic units dominate the footwall of the Plomosa Mountains core complex: 1) Orocopia Schist, 2) an early Miocene intrusive complex, and 3) gneiss. The quartzofeldspathic Orocopia Schist encompasses 10.5 km2 of the northern Plomosa Mountains, and locally contains graphitic plagioclase porphyroblasts, and coarse-grained green actinolite pods 0.2–1.5 m wide are scattered throughout the Orocopia Schist. These pods are high in Mg, Cr, and Ni, strongly suggesting derivation from an ultramafic protolith. A laterally continuous unit of amphibolite (~3.5 km long, 10–150 m thick), interpreted as Orocopia metabasalt, is localized along a moderately SE-dipping contact between the Orocopia Schist and the gneiss, and contains metachert layers 3–30 cm thick. L>S mylonitic fabrics are common throughout the Orocopia Schist and gneiss, and a zone of L-tectonites is localized along their contact. The Miocene intrusive complex, which is dominated by biotite granodiorite and hornblende diorite, parallels the detachment fault along its eastern margin, and the gneiss is corrugated about a NE-trending subhorizontal axis. Mylonitic fabrics have systematic NE-SW-trending lineations (average T/P = [220/09]), and record top-to-the-NE shear. The Plomosa detachment fault defines a broad NE-trending corrugation parallel to its slip direction, and on average dips ~12° to the NE. NW-striking normal faults, joints, and dikes throughout the footwall record NE-SW extension consistent with that of the mylonitic fabrics, indicating there was no change in extension direction between the ductile and brittle regimes. Dynamically recrystallized quartz grain sizes and mechanisms suggest the gneiss and the Orocopia Schist underwent amphibolite-facies mylonitization, locally with evidence of overprinting by upperto middle-greenschist-facies mylonitization, whereas the Miocene intrusive complex dominantly records upperto middle-greenschist-facies mylonitization. Based on the geometry and deformation conditions of footwall fabrics, three separate mylonitic shear zones were identified: I) A pre-Miocene, originally moderately NE-dipping (~50°) normal-sense shear zone which deformed the corrugated gneiss. II) An originally shallowly NE-dipping (~25°) normal-displacement Miocene shear zone, active before initiation of the detachment fault, and which primarily deformed the Orocopia Schist and Miocene intrusive complex. III) A detachment-subparallel Miocene shear zone that deformed rocks adjacent to the Plomosa detachment fault. The Miocene intrusive complex was mylonitized prior to exhumation by the Plomosa detachment fault, suggesting that magmatism slightly predated or was coeval with initiation of detachment faulting. U-Pb zircon geochronology of the Orocopia Schist reveals an abrupt drop-off of Th/U ratios >0.1 at 68–70 Ma, which demarcates the maximum depositional age of the Schist. A high density of Th/U ratios <0.1 between 75–50 Ma zircons record metamorphism of the Schist after it was subducted. Xenocrystic zircons in the Miocene intrusive complex have an identical distribution of ages and Th/U ratios as the Orocopia Schist, indicating that the Schist was melted or assimilated during early Miocene plutonism. The early Miocene pre-detachment paleo-depth of the top of the Orocopia Schist is 3–4 km, suggesting a Paleogene exhumation event brought the Schist to upper-crustal depths after it was subducted beneath the crust Late-stage dextral and sinistral faults strike N and ENE, respectively, and associated barite and carbonate veins strike NE. These faults locally cut moderately-consolidated colluvium, and veins cut NW-striking joints and faults associated with detachment faulting. Together these structures record a minor phase of WNW-ESE extension, which is attributed to regional post-middle Miocene dextral faulting, with the northern Plomosa Mountains having occupied a transtensional step.
Zip file contains plate 1.